Effects of transcutaneous electrical acupoint stimulation on gastrointestinal dysfunction after gastrointestinal surgery: A meta-analysis. (May 2023) - Jiang, Tingting; Li, Jianli; Meng, Lei; Wang, Jing; Zhang, Huanhuan; Liu, Meinv
Abstract: Background: Postoperative gastrointestinal dysfunction (PGD) is a common complication in patients undergoing gastrointestinal surgery. Several studies have evaluated the effect of transcutaneous electrical acupoint stimulation (TEAS) on PGD, so we conducted a systematic review and meta-analysis to better understand these studies methodologic limitations and summarize clinical effects. Methods: Articles (published from January 2010 to April 2022) were searched from the following databases: Wanfang Database, China National Knowledge Infrastructure (CNKI), Cochrane Library, PubMed, Web of Science and Embase. Two authors conducted literature selection, data extraction and statistical analysis independently. This meta-analysis used RevMan 5.4 software to implement statistical analysis and applied Cochrane bias risk tool to assess methodologic weaknesses of included articles. We assessed the effect of TEAS on time to first flatus, first defecation and bowel sound recovery through meta-analyses using a random-effects model. Results: The meta-analysis included 10 articles including 1497 patients. This study showed that TEAS could effectively promote postoperative gastrointestinal function recovery by analyzing the time to first flatus (MD−14.81 h, 95% CI −15.88 to −13.75 h), time to first defecation (MD−14.68 h, 95% CI −20.59 to −8.76 h), time to bowel sound recovery (MD−5.79 h, 95% CI −10.87 to −0.71 h), length of hospital stay (MD−1.48d, 95% CI −1.86 to −1.11d), and the incidence of postoperative nausea and vomiting (PONV) (OR 0.41, 95% CI 0.29–0.58). In addition, we assessed the quality of the articles and found small sample sizes and lower methodological quality in some articles. Conclusion: Our meta-analysis revealed that TEAS could be a nonpharmacological treatment for PGD in patients after gastrointestinal surgery. However, positive findings should be treated carefully and future studies with high quality and large samples are needed to support this results. Highlights: To explore effect of transcutaneous electrical acupoint stimulation (TEAS) on gastrointestinal dysfunction. TEAS improves postoperative gastrointestinal dysfunction. TEAS reduces duration of hospitalization. TEAS decreases the incidence of postoperative nausea and vomiting.